Practical application of real-time sub-seasonal monsoon onset forecasting and monitoring for decision-making - Thompson, Elisabeth M.; Wainwright, Caroline M.; Hirons, Linda C.; Woolnough, Steven J. (Frontiers in Climate, 2024)
Skilful monsoon onset forecasts are highly sought after in West Africa, due to the importance of monsoon onset for supporting agriculture, disease prevalence and energy provision. With the sub-seasonal timescale bridging the gap between weather and seasonal forecasts, sub-seasonal forecasts have the potential to provide useful decision-making information about the onset of the monsoon rainfall. This study explores sub-seasonal monsoon onset forecasts over Ghana using the European Centre for Medium Range Weather Forecasting (ECMWF) operational ensemble prediction systems. Three commonly used methods for defining monsoon onset are compared, and the benefits, challenges, and potential of real-time, sub-seasonal onset forecasting using these methods are examined. Monsoon onset forecasting at sub-seasonal timescales, and associated decision-making with shorter-term information can be challenging due to the typically single occurrence of rainfall onset within a season. Sub-seasonal forecasts of monsoon onset are shown to be particularly useful for confirming onset occurrence, at least 1–2 weeks earlier than when observations are used. Earlier confirmation of monsoon onset provided by sub-seasonal forecasts, has the potential for earlier decision-making and action that would positively impact sectors such as agriculture.